Pengembangan Komik Astronomi Digital Menggunakan Canva - Raisal, Abu Yazid; Ananda, Fadilla Sayu; Yuhyi, Rihan; Hasibuan, Alya Fathi Muhammad (Navigation Physics : Journal of Physics Education, 2024)
Astronomy learning is often considered difficult by most students of the Astronomy study program at the Universitas Muhammadiyah Sumatera Utara., so effective learning media in the form of digital comics is needed. This type of research is research and development (R&D), which follows the ADDIE (Analyze, Design, Development, Implementation, Evaluation) development procedure. This research is only limited to the development stage. Comics are developed using Canva because they are easy to use on all devices and provide many features that make it easy for users to create graphic designs. The validation results from media and material experts on the comics developed each have an average value of 91% and 92% or are included in the very good criteria. These results indicate that digital astronomy comics can be used in learning. This research is limited to the development stage, so its effectiveness in learning cannot be known. The effectiveness and practicality of this digital astronomy comic can be known through the implementation stage.